Purification of Human Factor IX by Chromatography of a Coagulation Factor Concentrate - Suomela, Hannu (Thrombosis and Haemostasis, 1976)
A purification procedure for, and some properties of, coagulation factor IX are described. The coagulation factor concentrate used for the treatment of hemophilia B patients was employed as the starting material. The isolation procedure consists of chromatography in DEAE-cellulose, two chromatographies in hydroxyapatite gel and two gel filtrations in Sephadex G-200. Only trace amounts of factors II, VII and X were present in the final preparation and the specific activity of factor IX was 159 corresponding 10,300 times purification from plasma. The molecular weight was estimated to be 76,000 in gel filtration and 86,000 in sodium dodecyl sulfate disc gel electrophoresis. Three activity peaks with pis 4.15, 4.25 and 4.40 were obtained by isoelectric focusing.